Stimulus-dependent effects on tactile spatial acuity - Tommerdahl M (Behavioral and Brain Functions, 2005)
Abstract Background Previous studies have shown that spatio-tactile acuity is influenced by the clarity of the cortical response in primary somatosensory cortex (SI). Stimulus characteristics such as frequency, amplitude, and location of tactile stimuli presented to the skin have been shown to have a significant effect on the response in SI. The present study observes the effect of changing stimulus parameters of 25 Hz sinusoidal vertical skin displacement stimulation ("flutter") on a human subject's ability to discriminate between two adjacent or near-adjacent skin sites. Based on results obtained from recent neurophysiological studies of the SI response to different conditions of vibrotactile stimulation, we predicted that the addition of 200 Hz vibration to the same site that a two-point flutter stimulus was delivered on the skin would improve a subject's spatio-tactile acuity over that measured with flutter alone. Additionally, similar neurophysiological studies predict that the presence of either a 25 Hz flutter or 200 Hz vibration stimulus on the unattended hand (on the opposite side of the body from the site of two-point limen testing – the condition of bilateral stimulation – which has been shown to evoke less SI cortical activity than the contralateral-only stimulus condition) would decrease a subject's ability to discriminate between two points on the skin. Results A Bekesy tracking method was employed to track a subject's ability to discriminate between two-point stimuli delivered to the skin. The distance between the two points of stimulation was varied on a trial-by-trial basis, and several different stimulus conditions were examined: (1) The "control" condition, in which 25 Hz flutter stimuli were delivered simultaneously to the two points on the skin of the attended hand, (2) the "complex" condition, in which a combination of 25 Hz flutter and 200 Hz vibration stimuli were delivered to the two points on the attended hand, and (3) a "bilateral" condition, in which 25 Hz flutter was delivered to the two points on the attended hand and a second stimulus (either flutter or vibration) was delivered to the unattended hand. The two-point limen was reduced (i.e., spatial acuity was improved) under the complex stimulus condition when compared to the control stimulus condition. Specifically, whereas adding vibration to the unilateral two-point flutter stimulus improved spatial acuity by 20 to 25%, the two-point limen was not significantly affected by substantial changes in stimulus amplitude (between 100 – 200 μm). In contrast, simultaneous stimulation of the unattended hand (contralateral to the attended site), impaired spatial acuity by 20% with flutter stimulation and by 30% with vibration stimulation. Conclusion It was found that the addition of 200 Hz vibration to a two-point 25 Hz flutter stimulus significantly improved a subject's ability to discriminate between two points on the skin. Since previous studies showed that 200 Hz vibration preferentially evokes activity in cortical area SII and reduces or inhibits the spatial extent of activity in SI in the same hemisphere, the findings in this paper raise the possibility that although SI activity plays a major role in two-point discrimination on the skin, influences relayed to SI from SII in the same hemisphere may contribute importantly to SI's ability to differentially respond to stimuli applied to closely spaced skin points on the same side of the body midline.